Unpacking Employee Performance: The Mediating Role of Job Satisfaction in Leadership and Support Models - Syifa-i Nurrohman; Dedi Muhammad Siddiq; Mariam Setapa; James Tembo (Institut Teknologi dan Bisnis Asia Malang, 2026)
This study examines the effects of servant leadership and perceived organizational support on employee performance, with job satisfaction acting as a mediating variable. Grounded in Social Exchange Theory, the study explains how supportive leadership behaviors and organizational support foster positive employee reciprocity through enhanced work attitudes and performance. A quantitative approach was employed using survey data from 200 employees in the poultry industry within an emerging economy. Data was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that servant leadership and perceived organizational support significantly and positively influence job satisfaction. Job satisfaction, in turn, improves employee performance and mediates the relationship between independent variables and performance outcomes. These findings highlight the importance of relational mechanisms in strengthening employee performance within organizational settings in emerging economies.